Presynaptic local signaling by a canonical wingless pathway regulates development of the Drosophila neuromuscular junction. - Miech, C.; Pauer, H.U.; He, X.; Schwarz, T.L. (Journal of Neuroscience, 2008)
Wnt/wingless signaling contributes to the development of neuronal synapses, including the Drosophila neuromuscular junction. Loss of wg (wingless) function alters the number and structure of boutons at this model synapse. Examining Wnt/wingless signaling mechanisms, we find that a distinct pathway operates presynaptically in the motoneuron and can account for many of the effects of wingless at this synapse. This pathway includes the canonical elements arrow/LRP (low-density lipoprotein receptor-related protein), dishevelled, and the glycogen synthase kinase shaggy (GSK3) and regulates the formation of microtubule loops within synaptic boutons as well as the number of synaptic boutons. This pathway, however, appears to be independent of beta-catenin signaling and the transcriptional regulation that is most frequently downstream of these components. Instead, inhibition of shaggy is likely to act locally. This pathway thus provides a parallel mechanism to the postsynaptic activation of frizzled receptors and indicates that synaptic development results from the bidirectional influence of wingless on both presynaptic and postsynaptic structures via distinct intracellular pathways.